“All I want is to be involved in my treatment”: Experiences of HIV treatment and viral load monitoring among adolescents, young adults and healthcare providers in Tanzania - Joan Rugemalila; Anna Minja; Magreat Somba; Adellah Sariah; Hellen Siril; Christopher Sudfeld; Tumaini Nagu; Bruno Sunguya; Said Aboud (PLoS ONE, 2025)
Background Virologic response is the earliest indicator of HIV treatment, making it the gold standard in monitoring treatment response. This study explored experiences and challenges of HIV treatment and viral load (HVL) monitoring among adolescents and young adults (AYA), parents or guardians of young adolescents and healthcare providers (HCPs). Methods This was a qualitative study conducted between March and May 2022 in five health facilities in an urban setting of Tanzania. We performed 20 in-depth interviews (IDIs) with AYA who had full HIV-positive status disclosure, 8 IDIs with parents or guardians of young HIV-infected adolescents, and five focus group discussions (FGDs) with 30 HCPs. The IDIs and FGD transcripts were translated from Swahili into English, transcribed, coded, and performed thematic analysis using NVivo software. Results AYA demonstrated an understanding of HIV treatment as lifelong and, most knew the benefits of HIV viral load (HVL) monitoring. It was apparent that 60% of older adolescents (15–19 years), parents or guardians, and young adults (20–24 years) discussed HVL results with HCPs and, the majority desire to be involved in their HIV treatment. HCPs reported that missing clinic appointments among AYA attending boarding schools or college contribute to delays in HVL testing and initiation of enhanced adherence counselling (EAC). Notably, HCP faced challenges recalling AYA who received three to six multi-month anti-retroviral drug (ARV) refills when their HVL results were high (VL ≥ 1000 copies/ml). Conclusions More than half of AYA expressed ownership in their HIV treatment; they discussed the meaning of their HVL results with HCPs. Additionally, AYA reported non-frequent challenges in HVL testing however, HCPs described missing appointments for AYA on three to six multi-months dispensing of ARVs as major challenges for implementing HVL testing. Importantly multi-months ARV dispensing in AYA needs program evaluation to inform the best implementation modality to support viral suppression.